Implementasi Etnosains dalam Pembelajaran IPA di SD Muhammadiyah Alam Surya Mentari Surakarta: Implementation of Ethnoscience in Science Learning at Elementary School of Muhammadiyah Alam Surya Mentari Surakarta - Puspasari, Afrin; Susilowati, Indah; Kurniawati, Lilis; Utami, Resiana Ridha; Gunawan, Indra; Sayekti, Ika Candra (Universitas Muhammadiyah Sidoarjo, 2019)
The swift flow of globalization has led to increasingly eroded Indonesian local cultural values. This has caused a shift in neglected cultural values and local wisdom. Therefore, an approach is needed, namely ethnoscience in the learning process. This study purposed to determine whether The Elementary School of Muhammadiyah Alam Surya Mentari has applied ethnoscience in science learning and describe the implementation of ethnoscience based on science learning in The Elementary School of Muhammadiyah Alam Surya Mentari. The method used was descriptive qualitative research design. The results of the study showed that the planning of science learning based on ethnoscience approach in This School was still unplanned, but the school had unconsciously implemented ethnoscience approach. The implementation of science based on ethnoscience learning was by integrating between the material with the environment, culture, and social in the environment. Evaluation of the implementation of ethnoscience based on science learning included cognitive, affective, and psychomotor evaluation in accordance with evaluation standards in the 2013 curriculum.